The potential benefit of road connectivity with kalimantan from international trade perspective: the effect of cultural affinity - Rafiq Idris; Kasim Mansur; Rizal Zamani Idris; Zuraidah Jamrin (Penerbit Universiti Malaysia Sabah, 2017)
In 2015, during the 27th ASEAN Summit in Kuala Lumpur, ASEAN Leaders announced for the establishment of the ASEAN Economic Community (AEC). For that purpose, an ASEAN Community Vision 2025 and the ASEAN Community Blueprints 2025 are being announced where it is being targeted for the period 2016-2025 and are intended to establish the ASEAN Political-Security Community, the ASEAN Economic Community and the ASEAN Socio-cultural Community. In this regard, will AEC further strengthen Sabah-Kalimantan trade relations? In relation to this, there was a proposal of establishing road connectivity between Sabah and North Kalimantan, where there was an idea to connect Serudung and Simanggaris via road. This indeed has a potential to add impetus for greater economic integration between Sabah and North Kalimantan under the framework of AEC. This study examines the effect of cultural affinity on Sabah’s export econometrically, based on Sabah’s 16 years of trade experience with each and every country of the world using gravity model. The finding of the study indicates that cultural affinity has positive effect on Sabah’s export.